A new species of Parmotrema (Parmeliaceae, lichenized Ascomycota) with lecanoric acid from the Cerrado of Maranho State, Northeast Brazil - Nascimento, Gildean Macedo [UNESP]; Dutra, Tamires Silva; Cunha-Dias, Iane Paula Rego (American Bryological and Lichenological Society, 2025)
A new species of Parmotrema, P. neoisidiatum, with medullary lecanoric acid, is here proposed as new to science. It has a foliose thallus with isidia mainly occurring on the margins of lobes, forming crenulations; lobes are 612 mm wide, with an eciliate margin, a bicolored (white and yellowish) medulla, and contains atranorin, lecanoric acid, and an unknown substance as the main medullary compounds. The species has a corticolous habit, found on branches of living and fallen trees in the cerrado stricto sensu and cerrado areas, both typical vegetations of the Cerrado biome in the state of Maranho, Brazil. Parmotrema neoisidiatum is considered potentially endangered according to our preliminary IUCN assessment. This work presents a description, illustrative images, conservation status, and a key to Parmotrema species with lecanoric acid in South America.